Youth Resilience review based on Religiosity and Social Support - Arafat HSB, M. Yasir; Netrawati, Netrawati; Daharnis, Daharnis; Marjohan, Marjohan (Universitas Negeri Padang, 2023)
This research is motivated by the presence of symptoms that appear in adolescents at the Bening Nurani Padang Foster Home who do not yet have the ability to make sense of the events and life events they experience and make adolescents sink and dissolve in misery, without the flexibility to rise.. Religiosity and social support are factors that are thought to influence adolescent resilience. Religiosity and social support are factors that are thought to influence adolescent resilience. This study aims to analyze: 1) religiosity, social support, and adolescent resilience, 2) the relationship between religiosity and adolescent resilience, 3) the relationship between social support and adolescent resilience, and 4) the relationship between religiosity and social support together with youth resilience. This research uses a quantitative descriptive correlational method. Respondents in this study were adolescents at the Bening Nurani Padang Foster Home. The research sample was taken as a whole from the existing population with a total of 97 people. The research instrument used a questionnaire with a Likert scale model. Data were analyzed with descriptive statistics, simple regression and multiple regression. The research findings show that: (1) on average, adolescent religiosity is in the high category, (2) social support is in the high category, (3) adolescent resilience is in the high category, (4)there is a positive and significant relationship between religiosity and adolescent resilience, (5) there is a positive and significant relationship between social support and adolescent resilience, and (6) there is a positive and significant relationship between religiosity and social support and adolescent resilience.